(untitled) (International Journal of Environmental Sciences, 2025)
The main purpose of the study was to determine the influence of digital social media platforms on the writing skills of fourth year BSEd English Language major students at Cebu Normal University. It also looked into how these platforms motivate students to increase their productivity and the extent to which social networking sites (SNS) aid in their English language proficiency. This study was conducted at Cebu Normal University (Main Campus) in the first semester of the academic year 2024–2025. Forty (40) students and five (5) instructors were chosen as samples, respectively. During the data analysis process, both qualitative and quantitative methodologies were used. The findings of the data revealed that digital social media platforms have several influence on tertiary students’ writing abilities, with more beneficial effects than unfavorable ones. The results demonstrated that both students and professors were able to create group discussions in which they could share resources connected to the course, exchange ideas, and encourage their students to complete projects that would help them improve their writing skills. Nevertheless, the results confirmed that digital social media platforms do not have some detrimental effects. Students’ formal writing is influenced by digital social media since they are now more accustomed to using short forms of words and using improper syntax and sentence structures. Findings revealed that students follow distinct writing trends on social media sites, which clearly deviate from standard English spelling. Students’ writing is influenced by social media terminology in both positive and negative ways. When students collaborate in groups, the results are favorable. However, when respondents write on their own, the effect is adverse. In addition, while there are advantages and disadvantages to using digital social media, students must appropriately encourage themselves to use social networking sites (SNS) in order to improve their English writing. Social Media platforms like Facebook, Twitter, Instagram. Linkedin and Tiktok have both positive and negative influence to tertiary students’ writing skills. Moreover, these platforms have been shown to improve student-teacher engagement and learning motivation while promoting inclusive and flexible learning. Digital feedback and teamwork have also been shown to be significant in the writing learning process. Qualitative research demonstrates that students’ writing abilities are improved by using digital social media platforms, which also increase writing quality, productivity, and active learning. The research highlights the significance of educational policies and methods that facilitate the full integration of digital technology in order to attain more effective and efficient higher education in the future, based on these findings. Thus, it’s critical to highlight how teachers may support their students in using social networking sites to enhance their writing abilities. Accordingly, this study proposes that both teachers and students can improve their English language skills if they use digital social media platforms appropriately.